2015
DOI: 10.1016/j.hydromet.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging characterisation of the influence of flowrate on liquid distribution in drip irrigated heap leaching

Abstract: Liquid irrigation is one of the key process control parameters following the construction of an ore leaching heap. This study uses 3D magnetic resonance imaging (MRI) to examine noninvasively the effect of liquid flowrate changes on heap hydrology when drip irrigation is used. Experimental results from a vertical column show that the increase in flowrate causes an increase in the number of rivulets in the ore bed. The new rivulets were found to be thicker, and their development caused an increase in liquid-sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Genomic engineering has been implemented to obtain targeted bacteria [21,22]. Additionally, the intervention of precise scanning and observatory technologies-such as computed tomography (CT), magnetic resonance imaging (MRI), particle image velocimetry (PIV), and others [23][24][25][26]-have improved on research. Some characterized models have been improved, like the lattice Boltzmann model (LBM) and so on [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic engineering has been implemented to obtain targeted bacteria [21,22]. Additionally, the intervention of precise scanning and observatory technologies-such as computed tomography (CT), magnetic resonance imaging (MRI), particle image velocimetry (PIV), and others [23][24][25][26]-have improved on research. Some characterized models have been improved, like the lattice Boltzmann model (LBM) and so on [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Neethling s team of Imperial College London innovatively used the suspension force measurement method to monitor the liquid holding behavior of the static ore particle pile system. Some computer tomography, nuclear magnetic resonance, and other techniques have also been applied to the liquid holding characteristics of unsaturated porous media stacking heap [23][24][25], but the above research findings are more static and transient without considering mineral leaching. Despite this, there are still few studies that both consider liquid hysteresis and solute transport in agglomerated leaching condition, leading to a research gap regarding a deep understanding of how agglomerated heaps enhance mineral leaching and solute transport intensification [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D MRI technique has also been adopted to study the effect of liquid flowrate changes on heap hydrology and control parameters during the bioleaching process, such as ferrous ion oxidation (Videla et al, 2016). Experimental results have shown that an increase in flowrate causes an increase in the number of rivulets in the leaching column (Fagan et al, 2013;Fagan et al, 2015). In addition, 3D imaging technologies, such as X-ray computed tomography (CT) and positron emission tomography (PET), have also been applied in heap leaching Wildenschild and Sheppard, 2013).…”
Section: Introductionmentioning
confidence: 99%